The euro and its threat to the future of Europe - Stiglitz, Joseph E. (London, 2016)
"Solidarity and prosperity fostered by economic integration: this principle has underpinned the European project from the start, and the establishment of a common currency was supposed to be its most audacious and tangible achievement. Since 2008, however, the European Union has ricocheted between stagnation and crisis. The inability of the eurozone to match the recovery in the USA and UK has exposed its governing structures, institutions and policies as dysfunctional and called into question the viability of a common currency shared by such different economies as Germany and Greece.